2009
DOI: 10.1111/j.1440-1843.2008.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐pitched breath sounds indicate airflow limitation in asymptomatic asthmatic children

Abstract: Higher HFI in asymptomatic asthmatic children may indicate small airway obstruction. Additional ICS treatment may improve the pulmonary function indices representing small airway function with simultaneous HFI decreases in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…These studies of breath sounds in asthmatic conditions have demonstrated that breath sounds are affected by changes in generation or transmission . We reported in 2009 that the intensity of inspiratory lung sounds reflects airway obstruction in asymptomatic asthmatic children . When the intermediate‐frequency components of lung sounds are transferred to the chest wall, the ic700 increases, implying that there is asthmatic airway dysfunction even when children are asymptomatic.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies of breath sounds in asthmatic conditions have demonstrated that breath sounds are affected by changes in generation or transmission . We reported in 2009 that the intensity of inspiratory lung sounds reflects airway obstruction in asymptomatic asthmatic children . When the intermediate‐frequency components of lung sounds are transferred to the chest wall, the ic700 increases, implying that there is asthmatic airway dysfunction even when children are asymptomatic.…”
Section: Discussionmentioning
confidence: 92%
“…Lung sound analysis is a non‐invasive method that does not require the cooperation of infants. Recent developments in signal processing methods have improved the extraction of physiologically and clinically relevant information from lung sounds …”
Section: Introductionmentioning
confidence: 99%
“…Results of previous reports suggested that an LSA can be useful for predicting airway constriction or airway hyperresponsiveness. [5][6][7][8][9][10] There are 2 possible reasons for the increase in the E-I LF: one is that the airflow is increased by the narrowing of the airway, and the other is that turbulence is caused by the airway mucosal edema associated with asthmatic inflammation. 13 It was interesting that the E-I LF was the only significant independent factor related to the airway eosinophil count in the multiple regression analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Each of the highest frequencies at inspiration or expiration is inversely correlated with airway obstruction. 9,10 Notably, airway inflammation is an important factor in the diagnosis and/or evaluation of the effects of treatment of patients with asthma. The degree of airway inflammation is now assessed by performing a bronchial biopsy and a bronchial lavage with a fiberoptic bronchoscope, which are invasive; by inducing sputum by using a hypertonic saline solution inhalation, which is cumbersome or unstable to be obtained; and by analyzing exhaled breath condensate or measuring exhaled nitric oxide (FeNO), which are expensive.…”
mentioning
confidence: 99%
“…19 The majority of breath sounds have frequencies of 200–250 Hz, except for wheezes and crackles, which have frequency spectra of 100–1000 Hz and 200–2000 Hz, respectively. 20,21 All audio-video editing was done with iMovie version 10.0.4 (Apple Inc, Cupertino, California).…”
Section: Methodsmentioning
confidence: 99%